THE EFFECT OF EMPLOYEE SHARE PRICE EXPECTATIONS AND EMPLOYEE SHARE OWNERSHIP SATISFACTION ON EMPLOYEE ORGANIZATIONAL COMMITMENT AT PT. TELKOMUNICATIONS INDONESIA, TBK - Ardiansyah Adil Hanif; H Syamsul Alam; Fauziah Umar (Scientia Integritas Utama, 2023)
The employee stock ownership program known as ESOP is one of the efforts for companies to retain their best employees as well as to increase their work commitment which is a form of employee organizational commitment. As owners of company shares, of course, employees have expectations of the stock price so that they can benefit from the share ownership while increasing satisfaction with employee stock ownership. This research was conducted on employees at PT. Telekomunikasi Indonesia, Tbk, as one of the largest telecommunications operators in Indonesia, implemented the ESOP policy in June 2013. This study aims to examine the effect of employee stock price expectations on employee stock ownership satisfaction and examine the effect of these two variables on employee organizational commitment. The analytical method used is descriptive analysis, correlation analysis and path analysis. The results showed that the expectation of employee stock price had a significant positive effect on employee stock ownership satisfaction, employee share ownership satisfaction and employee stock price expectations had a significant positive effect on employee organizational commitment.